EFEKTIVITAS MODEL PEMBELAJARAN PEMECAHAN MASALAH DALAM PEMEBALAJARAN MATEMATIKA DI SEKOLAH DASAR - Yulita Dwi Lestari; Ristika Ristika (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2018)
This research was motivated by the low learning outcomes of students in mathematics learning. This study aims to improve student learning outcomes in mathematics learning in class V Baitul Jannah Elementary School in Bandar Lampung by using a problem-based learning model. The research method used by the researcher is classroom action research in collaboration with fifth-grade teachers at Baitul Jannah Elementary School in Bandar Lampung, with a total of 25 students in grade V consisting of 10 male students and 15 female students. This research took place in 3 cycles, each cycle consisting of 3 actions. The techniques used in data collection are observation, tests, interviews, documentation, and field notes. The results showed that the application of problem-based learning models can improve student learning outcomes in mathematics learning in class V SD Baitul Jannah Bandar Lampung.